Levantamento de falhas em prótese parcial fixa: acompanhamento de um ano - Izza, Pâmella Nóbrega [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Rehabilitation performed with Fixed Partial Denture (FPD) is a long procedure and generates expectations for the patient and the professional. Success can be measured by patient satisfaction with the esthetics and function achieved by rehabilitation treatment. However, failures can also be observed. This study aimed to evaluate the satisfaction of patients rehabilitated with fixed partial denture and failure rates - clinical complications - of prostheses installed after one year in patients treated at the School of Dentistry of Araçatuba - UNESP. After screening, 62 patients answered a questionnaire involving the level of satisfaction with the dental care and maintenance of prostheses. Then, they were submitted to clinical and radiographic evaluation. Gender, age, educational level, mechanical and biological failures were variables used for association with the responses obtained from the interviewees. For statistical analysis, chi-square and Fischer tests were employed. There was a statistically significant association between level of satisfaction and mechanical failures (p=0.04). On the other hand, the variables (gender, educational level, age and biological failures) were not statistically significant (p>0.05). As results, 17 patients said that they were not satisfied (27.42%), 23 evaluated the treatment as good (37.10%) and 22 claimed that the prosthesis is properly installed (35.48%). From the total of interviewees, 74.00% reported that do not have difficulties to perform the hygiene of the prosthesis. Mechanical failures were found (9.6%) and the most common was cement loosening, presented in four cases (57.14%). Fracture of ceramic in two cases (28.57%) and only one case of abutment tooth fracture (14.29%). Biological failures were observed in 30.65% of patients, and gingival recession (52.00%) was the most common. Periodontal...

A reabilitação realizada com Prótese Parcial Fixa (PPF) é um procedimento longo e que gera expectativas para o paciente e profissional. O sucesso pode ser avaliado pela satisfação do paciente com a estética e função alcançadas pelo tratamento reabilitador. Entretanto, falhas ou insucessos também podem ser observados. Este trabalho teve como objetivo avaliar a satisfação dos pacientes reabilitados com prótese parcial fixa e a incidência de falhas - complicações clínicas - das próteses instaladas após um ano, nos pacientes atendidos na Faculdade de Odontologia de Araçatuba - UNESP. Após triagem, 62 pacientes responderam a um questionário abrangendo o grau de satisfação pelo tratamento odontológico e cuidados de manutenção para conservação das próteses. Em seguida, as mesmas foram submetidas à avaliação clínica e radiográfica. Sexo, faixa etária, escolaridade, falhas mecânicas e falhas biológicas foram variáveis utilizadas para associação com as respostas obtidas dos questionários. Para análise estatística, testes de Qui-quadrado e Fischer foram empregados. Houve associação estatisticamente significante entre grau de satisfação e falhas mecânicas (p=0,04). Porém, as demais variáveis (gênero, nível educacional, faixa etária e falhas biológicas) não apresentaram significância estatística (p>0,05). Como resultados, 17 pacientes afirmaram estar insatisfeitos (27,42%), 23 avaliaram o tratamento como bom (37,10%) e 22 alegaram que a prótese instalada está ótima (35,48%). Dos entrevistados, 74% informaram não apresentar dificuldades para a realização da higiene da prótese. Foram encontradas 9,67% de falhas mecânicas, sendo a mais comum a descimentação - prótese solta - apresentada em quatro casos...
Keywords: Satisfação do paciente; Pacientes; Reabilitação; Patient satisfaction